Understanding Persistent Non-compliance in a Remote, Large-Scale Marine Protected Area - Collins, Claire; Nuno, Ana; Broderick, Annette; Curnick, David J.; de Vos, Asha; Franklin, Thomas; Jacoby, David M. P.; Mees, Chris; Moir-Clark, James; Pearce, John; Letessier, Tom B. (Frontiers in Marine Science, 2021)
Area coverage of large-scale marine protected areas (LSMPAs, >100,000 km2) is rapidly increasing globally. Their effectiveness largely depends on successful detection and management of non-compliance. However, for LSMPAs this can be difficult due to their large size, often remote locations and a lack of understanding of the social drivers of non-compliance. Taking a case-study approach, we review current knowledge of illegal fishing within the British Indian Ocean Territory (BIOT) LSMPA. Data stemming from enforcement reports (2010-20), and from fieldwork in fishing communities (2018-19) were combined to explore and characterise drivers of non-compliance. Enforcement data included vessel investigation reports (n=188), transcripts of arrests (20) and catch seizures (58). Fieldwork data included fisher interviews (95) and focus groups (12), conducted in two communities in Sri Lanka previously associated with non-compliance in BIOT LSMPA. From 2010 to 2020, there were 126 vessels suspected of non-compliance, 76% of which were Sri Lankan. The majority of non-compliant vessels targeted sharks (97%), catching an estimated 14,340 individuals during the study period. Sri Lankan vessels were primarily registered to one district (77%) and 85% operated from just two ports within the fieldwork sites. Social Network Analysis (SNA) showed that 66% of non-compliant vessels were linked by social ties, including sharing crew members, compared with only 34% of compliant vessels. Thematic analysis of qualitative data suggested that perceptions of higher populations of sharks and social ties between vessels may both be important drivers. We discuss our findings within a global context to identify potential solutions for LSMPA management.